POLITISASI AGAMA PILKADA DITINJAU DARI PERSPEKTIF AGAMA KRISTEN - minerva gabriela tuanakotta (STT Bethel The Way, 2021)
This research aims to reveal about the politicization of religion in DKI Jakarta election from a Christian perspective. Indonesia, a country that is diverse, religious, and has God, must carry out its identity in politics. The implication of Indonesia as a country that is diverse, religious, and godly is the proliferation of political parties with religious ideologies along with various efforts to politicize religion. A study must be conducted to break the vicious circle that threatens the welfare and pluralism of the Indonesian nation, because the politicization of religion is the root of the problem. One of the cases of politicization of religion in Indonesia is the DKI Jakarta Pilkada. The method study of the politicization of religion uses a qualitative approach by collecting literature review data. The politicization of religion in the DKI Jakarta Pilkada was found to have brought politics further away from ideal conditions such as achieving harmony, justice, and prosperity. The results of the study show that politics and religion cannot be separated, in fact if the relationship between politics and religion is in the right position, it can create ideal and perfect conditions. The conclusion that can be conveyed is that politics will remain a dark world even though it has been filled with good values, so that the important role of believers is very real in the political world, because only believers are able to provide light to achieve perfect ideal conditions in politics. . Keywords: Politics, Pilkada, Christianity